Strangers in the Frame: Inside and Outside the Cent Nouvelles nouvelles. Issue 3 (30th May 2018) - Emerson, Catherine
Abstract: This article examines the way in which tales of the Burgundian Cent Nouvelles nouvelles are interpreted differently by different reading publics. Taking a neglected tale in the corpus, nouvelle 66, as a starting point, the article argues that this nouvelle exemplifies tendencies observable throughout the collection, particularly in regard to surprising physical characteristics of outgroup members such as women and clerics. Viewed in the context of the tales' original readership, such stories cement ingroup solidarity amongst a group of elite men who, whilst sharing some characteristics, were reasonably diverse in a number of ways. However, the original reading context is not fully reconstructable because it is unclear as to what the narrative frame actually represents. Once the tales move beyond this frame, the court of Philippe le Bon becomes a spectacle itself, and this is reflected in a number of readings which censure the original audience. The article argues that this reaction is present in the very first edition and is indeed inherent in the narrative frame of the Cent Nouvelles nouvelles .